Maturation-related differences in adaptations to resistance training in young male swimmers - Moran, J.; Sandercock, G. R. H.; Ramirez-Campillo, R.; Wooller, J.-J.; Logothetis, S.; Schoenmakers, P. P. J. M.; Parry, D. A. (The Journal of Strength and Conditioning Research, 2018)
This study examined the effects of resistance training on muscular strength and jump performances in young male swimmers. It was hypothesized that adaptations would be of a lower magnitude in less mature (prepeak height velocity [PHV]) than in more mature (post-PHV) subjects. Fourteen pre-PHV (-1.8 ± 1.0 years) and 8 post-PHV (1.6 ± 0.5 years) swimmers undertook a 30 minutes, twice-weekly resistance training program for 8 weeks. They were compared with matched control groups (pre-PHV: -2.0 ± 1.1, n = 15; post-PHV: 1.2 ± 1.0, n = 7). The effects on lower-body isometric strength (LBS), measured with midthigh pull, and vertical jump (VJ) height in the post-PHV group were large (effect size: 1.3 [0.4 to 2.2]) and small (0.4 [-0.4 to 1.2]), respectively. Effects on LBS and VJ height in the pre-PHV group were moderate (0.8 [0.1 to 1.4]) and trivial (0.2 [-0.5 to 0.8]), respectively. Estimates in the post-PHV control group (LBS: 0.7 [-0.2 to 1.6]; VJ: 0.2 [-0.7 to 1.0]) and the pre-PHV control group (LBS: 0.1 [-0.5 to 0.7]; VJ: -0.3 [-0.9 to 0.3]) may indicate the extent to which maturation could contribute to the performance changes seen in the respective training groups. Lower-body isometric strength and VJ are trainable, but to different magnitudes, in pre- and post-PHV swimmers. After appropriate foundational training to establish technical competency, twice-weekly resistance training sessions of 30 minutes duration, comprising 3 sets of 4 exercises can be effective in pre- and post-PHV youth.